TEACHERS’ PERCEPTION ON STUDENTS’ LEXICOGRAMMATICAL ERRORS IN THEIR E-MAIL WRITING IN SECOND SEMESTER ROOM DIVISION CLASS IN BALI TOURISM INSTITUTE BASED ON TEACHERS’ GENDER AND LEVEL OF EXPERTISE - Susanti, Luh Eka; Padmadewi, Ni Nyoman; Budasi, I Gede (Universitas Pendidikan Ganesha, 2013)
Abstract This study aimed at 1) analyzing the forms of the students? lexicogrammatical errors, 2) analyzing the teachers? correction on the students? lexicogrammatical errors, and 3) describing the teachers ?perception on the students? lexicogrammatical errors whether it is a normal thing as a part of learning or as an obstacle which hinder the students? progress. The subjects were two English teachers and second semester Room Division students. This study was designed in the form of descriptive qualitative research and the instruments being used were human instrument, questionnaire, and interview. The findings show that 1) there were 19 categories of errors that occurred in the students? writings, 2) both of the subjects used direct correction, but there were some similarities and differences in the forms and the functions, and 3) the teachers? perceptions were classified into 4 major points, namely perception on writing and its problems, perception on the nature of lexicogrammatical errors, perception on the value of errors, and perception on the sources of errors. Keywords: lexicogrammatical errors, teachers? correction, teachers? perception